Symetryczność prawa do podatków - Gavrilûk, Ruslana (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The symmetry of human right to taxes is an attributive, the most fundamental property of the right of man to taxes manifested both in space and in time. Spatial symmetry of human right to taxes is revealed in regularities and nature of the relationship of different subjects in tax legal relations: if a person comes up with claim then the other person compulsorily has a legal obligation with respect to the first one, and vice versa. The analysis of the force of human right to taxes also indicates the phenomenon of symmetry of opposites within time, though in a given case not interpersonal but temporal. If in initial quantum of the human right to taxes some person was a claimer, then in the next quantum of human right he unavoidably becomes a self-liable party. And vice versa, the party having been self-liable, becomes a claimer, and the claimer becomes a self-liable party.
Keywords: symetria prawa człowieka do podatków; przestrzenna symetria praw człowieka do podatków; czasowa symetria prawa człowieka do podatków; prawo do roszczeń; podatek